HEALTH SERVICES IN BAGHDAD DURING THE AGE OF ETHID AL-DAWLA AL-BUWAIHI 324-372 AH, 936-983 AD - Assistant Lecture Manal Mohammed Matar (Scholars Digest Publishing, 2024)
This paper will look into the Bimaristan of Ethid Al-Dawla Al-Buwaihi in Baghdad under the Buwaihi and stress its significance in the development of medical services and health systems at that time. The paper, by referring to several sources, describes how Bimaristan came into being, was organized and administered, and played a crucial role in the progress of medical science because of the contribution of Arab and non-Arab physicians and the patronage of the government. Bimaristan, in terms of its administration, the supervision of physicians by the Muhtasib, and the care that was provided, will be returned. The institution is at the heart of initiatives that flourished regardless of political instability, denoting an exceptionally dedicated society of Baghdad towards health and cleanliness during its so-called dark ages. It is one phase in history where different cultural backgrounds had made enormous progress in the practice of medicine, contributing major advancements to the medical legacy of the region.
Keywords: Ethil Al-Dawla Al-Buwaihi, Medical History ,Baghdad Health Services Physicians